The deviation of the long body axis from the vertical in Vertical and Vertical Bent Knee positions in synchronized divers - Habiera, M.; Rostkowska, E.; Antosiak-Cyrak, K. (Human Movement, 2006)
Purpose. The Vertical and Vertical Bent Knee positions are the basic positions in technical training of synchronized divers. The proper performance of these positions depends on the correct technique of arm movements and proper, i.e. vertical, positioning of the long axis of the body. The purpose of the study was to calculate the degree of deviation from the vertical of the long axis of the body in the Vertical and Vertical Bent Knee positions, depending on the age and sports level of synchronized divers. Basic procedures. 17 divers were video-filmed with the use of an underwater camera when performing the Vertical and Vertical Bent Knee positions. The recorded images were computer-processed with the Avi Image software. Main findings. Significant deviation of the straight line drawn through the axes of hip joints and shoulder joints from the vertical line was found in most subjects. Also, the position of the head in relation to the vertical and to the long axis of the body was varied and often incorrect. Conclusions. Underwater observation and computer analysis of selected elements of the movement technique in synchronized divers make it possible to find and assess errors otherwise unnoticed during above-water observation. Even very early, at the initial stage of the training process, instruments aimed at correcting the head position in relation to the body should be used, as well as a number of on-deck exercises which will facilitate the ability to maintain the proper vertical position of the body.